PROVISION COMBINATION OF LEMON AROMATHERAPY AND WARM GINGER DRINK FOR REDUCING NAUSEA AND VOMITING TO PREGNANT WOMENIN FIRST TRIMESTER - Wenny Indah Purnama Eka Sari; Kurniyati Kurniyati; Yusniarita Yusniarita (Proceeding B-ICON, 2022)
Nausea and vomiting is an usual phenomenon and common in the first trimester of pregnancy. Nausea usually occurs in the morning, but also can occur at night or any time. This can occur in the first four weeks to the twelfth week of pregnancy. Management of nausea and vomiting during pregnancy can be done with pharmacological and non-pharmacological therapy. Non-pharmacological therapy to reduce nausea and vomiting are lemon aromatherapy and warm ginger drink. This study aims to determine the Effect Combination of Giving Lemon Aromatherapy and drink warm ginger to reducing nausea and vomiting in first trimester pregnant women at Community Health Center Perumnas Rejang Lebong Regency in 2022. This research used quasy experimental study of pre-posttest design. The population was all pregnant mothers in first semester who experienced emesis gravidarum. The samples were 42 respondents by using permuted blocks technique. Collecting the data was conducted directly through the observation lemon aromatherapy and drink warm ginger 2 times for 4 days questionnaire by PUQE. Data analysis used statistical test of paired t-test and t-test. The result of the study before and after intervention of showed that the score was ?= 0.000 (? < 0.05), there was an effect combination of lemon aromatherapy and drink warm ginger on nausea and vomiting in pregnant women. Provision Combination of Lemon Aromatherapy and drink warm ginger more effective can reduced nausea and vomiting and the severity of nausea and vomiting in pregnant women.